Efektivitas Model Discovery Learning dalam Meningkatkan Kemampuan Berpikir Kritis Siswa SMP Negeri 2 Dayun - Marhamah, Marhamah; Fatmawati , Yenni; Mazianto, Mazianto (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the effectiveness of the Discovery Learning model in enhancing students' critical thinking skills at SMP Negeri 2 Dayun. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection in two cycles. The subjects are eighth-grade students who struggle to develop critical thinking skills through conventional teaching methods. Data were collected through observations, interviews, critical thinking skill tests, and documentation. The findings indicate that implementing the Discovery Learning model significantly improves students' critical thinking abilities. In the first cycle, critical thinking skills increased by 22%, while in the second cycle, they improved by 40%. The Discovery Learning model encourages students to actively explore concepts, ask questions, and discover solutions independently, thereby enhancing their understanding and critical thinking skills. This study concludes that Discovery Learning is an effective instructional model for improving students' critical thinking skills at the junior high school level.